Atomically dispersed supported metal catalysts: perspectives and suggestions for future research. Issue 19 (30th August 2017) - Gates, Bruce C.; Flytzani-Stephanopoulos, Maria; Dixon, David A.; Katz, Alexander
Abstract : Catalysts consisting of metal atoms that are atomically dispersed on supports are gaining wide attention because of the rapidly developing understanding of their structures and functions and the discovery of new, stable catalysts with new properties. Abstract : Catalysts consisting of metal atoms that are atomically dispersed on supports are gaining wide attention because of the rapidly developing understanding of their structures and functions and the discovery of new, stable catalysts with new properties. Our goals in this essay are to summarize the classes of these catalysts, to state key questions about them, to point out crucial methods for their characterization, and to suggest directions for future research. Most of the catalysts in this class incorporate supports that are inorganic materials such as metal oxides and zeolites, and the list of supports has recently been expanded to include small assemblies of metal atoms within molecular metal clusters, as well as the surfaces of bulk metals, including single crystals and supported nanoparticles. Scanning transmission electron microscopy and scanning tunneling microscopy have recently provided numerous images of isolated metal atoms on support surfaces, and complementary spectroscopic results have provided evidence of the metal oxidation states (usually positive, unless the support is a metal), metal–support bonding, and the ligands present on the metal. Catalysts in this class have been found to have activity for numerous reactions, including hydrogenations, oxidations, and the water gas shift. Some offer exciting new catalyst selectivities associated with the isolation of the metal centers within controllable environments. Some atomically dispersed supported metal catalysts, exemplified by those supported on zeolites, have nearly uniform arrays of metal sites that are considered to be nearly ideal catalytic sites, and these are excellently suited to investigation by theory, such as density functional theory, to fill in gaps left by experiment, to predict new properties, and to help guide future research.